EKSPLORASI ARSITEKTUR, RUMAH ADAT LANGWAH DI DESA WAISIKA KECAMATAN ALOR TIMUR LAUT KABUPATEN ALOR - Sifra Eunike Lauring; Silas Maniata; Silpa Bilha Fanau; Serlin Meri Letding; Sintike Melani Mauyaru; Halena Muna Bekata; Siria Mei Kamutlaka; Silpa Maiko; Petrus Mau Tellu Dony (CV. ADIBA ASIHA AMIRA, 2025)
This research aims to explore the architecture of Langwah Traditional House in Waisika Village, Alor Timur Laut Sub-district, Alor Regency, which is one of the cultural heritages that must be preserved. This research uses a qualitative method with an ethnographic approach. Data collection techniques were carried out through field observations, documentation and interviews with traditional leaders, Mr Arkadius Manimau. The data analysis technique used is qualitative descriptive analysis. The results obtained from this research show that the Langwah Traditional House is built with natural materials such as eucalyptus, alang-alang, and bamboo, and applies traditional construction techniques that consider adaptation to the environment. The layout of this traditional house consists of several parts with specific functions, such as storage for heirlooms, food ingredients, and traditional meeting rooms.